One-year cardiovascular risk assessment after laparoscopic sleeve gastrectomy: A retrospective cohort study (Annals of Medical Research, 2026)
Aim: Bariatric surgery effectively reduces cardiovascular risk, though the mechanisms remain incompletely understood. This study aimed to evaluate changes in Framingham cardiovascular risk scores and identify predictors of risk reduction following sleeve gastrectomy.Materials and Methods: This retrospective cohort study included 111 patients (73% female; median age, 33 years [range 18–63]; median BMI, 43 kg/m² [range 35–77]) who underwent laparoscopic sleeve gastrectomy between January 2021 and June 2024. Framingham 10-year cardiovascular disease risk scores were calculated at baseline and 12 months postoperatively. Multivariable linear regression identified independent predictors of absolute risk reduction.Results: The Framingham risk score decreased from 6 (-10–25) to 3 (-9–26) at 12 months (p < 0.001), representing a 50% relative risk reduction. BMI decreased from 43 (35–77) to 29 (21–55) kg/m² (p < 0.001). Notably, change in BMI was not correlated with cardiovascular risk reduction (r = 0.032, p = 0.735). HDL cholesterol demonstrated a biphasic trend—initially decreasing at 3 months, then exceeding baseline values at 12 months (p < 0.001). In multivariable analysis, age (β = -0.223, p < 0.001); baseline Framingham score (β = 0.532, p < 0.001); and HDL change (β = 0.279, p = 0.047) were independent predictors of the absolute risk reduction. Interestingly, an increase in HDL showed a negative association in univariable analysis but a positive association in multivariable analysis.Conclusion: Sleeve gastrectomy achieved a significant reduction in cardiovascular risk independent of the magnitude of weight loss. The HDL paradox and age-dependent response suggest that complex mechanisms beyond simple weight reduction are involved. These findings support incorporating cardiovascular risk assessment, not just BMI, when determining surgical indications.
Keywords: Sleeve gastrectomy; Framingham risk score; Cardiovascular risk; HDL paradox; Bariatric surgery; Weight loss